Pengenalan Dalam Penataan Laporan Keuangan Bersumber Dalam SAK-EMKM Pada UMKM Di Desa Panaggahan - Fauziah Nur Hutauruk; Komala Dewii; Khairunnisa Khairunnisa; Mirwansyah Putra Ritonga; Septia Nigustira (CV. Armas Suan Sejahtera, 2025)
Bookkeeping for MSMEs is required by the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). Recording and reporting are certainly significant obstacles for business actors. One obstacle often faced by MSMEs is the lack of financial data that can be used to apply for funding from banks and other financial institutions. The purpose of this community service (PkM) activity is to teach and train participants in preparing financial reports in accordance with SAK EMKM. The activity method is divided into three main stages: identifying needs, providing instructions or simulations for preparing financial reports and interactive discussions, and providing practical support and assessments. To ensure the material is easily accepted and used by MSMEs, a participatory approach is used. Based on the results of the activity, the interactive training accompanied by intensive mentoring was able to improve participants' understanding and ability in preparing basic financial reports, as well as improving partners' understanding of SAK EMKM and their understanding of accounting recording and reporting.